An investigation of the penetration of lipids in the bilayer of stratum corneum - Suhaimi , Hamdan; Friberg, Stig E. (1989)
Water is an essential component of the animal body and the prevention of its escape into the surrounding atmosphere is one of the important functions of the skin. The main barrier to water transport through skin is located in the outermost layer, the stratum Corneum (1,2). In this study, small angle X-ray diffractometry is used to determine the interlayer spacing in the layered structure and optical microscopy with polarized light is applied to give information about liquid crystal/crystal variations. Samples for the X-ray analysis were prepared by adding the lipids accordingly and water content for each series was varied from 30% to 40% water. The samples were mixed by centrifuging repeatedly through a constriction in a sealed 7 mm glass tube. The samples were then allowed to equilibrate at 30°C for 24 hours. Samples for photomicrography were prepared by transferring a small amount of sample onto a glass slide and sheared between the slide and cover to a thickness of about 5 to 10 microns and was observed between cross polarizers and photographed at a magnification of 200 times. Results showed that the unsaturated fatty acid/soap combination gave a lamellar liquid crystal. The optical appearance is typical of lamellar liquid crystal. Addition of the saturated fatty acids showed a typical optical pattern of a distorted lamellar liquid crystal due to the presence of crystalline lipidic material. The addition of cholesterol obviously returned the structure to the liquid crystalline state. Results of small angle X-ray diffractograms are given in Figure 1. The interlayer spacing of the unsaturated fatty acid/soap increased from 45.8A to 49.0A. Addition of the saturated acids caused no significant change in the interlayer spacing nor in the dependence on the water content. The behaviour after addition of cholesterol was entirely different and a strong dependence on the water content was found with an increase of 4A at the lowest water content but an increase of 10A at the highest water content.